There's No Place Like Home: Black Women's Activism and Knowledge Construction in the Environmental Justice Movement - Tuere A. Bowles (Adult Education Research Conference, 2006)
This qualitative study explored Black women's activism and their process of learning and constructing knowledge in the environmental justice movement. By conducting in-depth interviews with sixteen activists from three southeastern states, findings revealed that a passion for home/place energized Black women's activism and served as the epicenter for knowledge construction.
Keywords: Black women' s learning; home/place; knowledge construction; social movements; environmental justice